(untitled) (International journal of medical sciences, 2026)
Epilepsy that starts in older people usually involves partial seizures that are either linked to a clear cause or unexplained. It's often tied to other health issues, both physical and mental, and can typically be managed with smaller daily doses of anti-seizure medications. Choosing the right treatment depends on the type of seizure, the overall epilepsy category, any other illnesses, and what other drugs the person is taking. Doctors often prefer medications that don't get broken down much in the body—like gabapentin, levetiracetam, and pregabalin—along with slow-release versions, which seem especially helpful for middle-aged and senior folks.